1995
DOI: 10.1007/bf01876206
|View full text |Cite
|
Sign up to set email alerts
|

The significance of fathers for inner-city African-American teen mothers

Abstract: Using the accounts of family life in young women's life stories, this qualitative study examined experiences with biological fathers for a sample of inner-city African-American teen mothers and a comparable sample of young women who were not parents. Distinguishing findings emerged about the pattern of young women's residential history with fathers, activity and interactions with fathers, and feelings about fathers. These qualitative findings were discussed in terms of their implications for services, policy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Zimmerman, Steinman, and Rowe (1998), on the other hand, found that father support helped African American male youth overcome risks associated with violent behavior. Other research has found that perceived father support was related to positive outcomes for African American adolescent girls (Caldwell et al, 1997;Chadiha & Danziger, 1995). These findings suggest that examining the influences of both parents may be vital to understanding family risk and protective factors associated with youth risk behaviors such as alcohol use among African American adolescents.…”
Section: Parental Support and Youth Substance Use Behaviormentioning
confidence: 83%
See 1 more Smart Citation
“…Zimmerman, Steinman, and Rowe (1998), on the other hand, found that father support helped African American male youth overcome risks associated with violent behavior. Other research has found that perceived father support was related to positive outcomes for African American adolescent girls (Caldwell et al, 1997;Chadiha & Danziger, 1995). These findings suggest that examining the influences of both parents may be vital to understanding family risk and protective factors associated with youth risk behaviors such as alcohol use among African American adolescents.…”
Section: Parental Support and Youth Substance Use Behaviormentioning
confidence: 83%
“…Emphasis has been placed on African American mothers when examining the influence of parental support because of the disproportionate number of female-headed households in African American communities. Recent research, however, has highlighted the role that African American fathers play in the lives of adolescents, even when they do not reside in the same household (Caldwell, Antonucci, Wolford, & Osofsky, 1997;Chadiha & Danziger, 1995;Salem, Zimmerman, & Notaro, 1998;Thomas et al, 1996;Zimmerman, Salem, & Maton, 1995;Zimmerman, Salem, & Notaro, 2000).…”
Section: Parental Support and Youth Substance Use Behaviormentioning
confidence: 99%
“…The majority of African American teen mothers do not reside with their own fathers and tend to regard their fathers more negatively than do teens without children (Chadiha & Danziger, 1995). Similarly, in the present study, maternal relationships with their own fathers predicted paternal involvement—those mothers who had good relationships with their own fathers were more likely to have father contact in their children's lives.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 118 articles, 31 (26%) in this review were about adolescent noncustodial fathers. The authors of these articles described (a) the subjective meaning of adolescent fatherhood (Hendricks & Montgomery, 1983), (b) adolescent parental involvement (Anthony & Smith, 1994;Miller, 1997;Strom et al, 2000), (c) the adolescent father's impact on the psychosocial development of his children (Cervera, 1991;Chadiha & Danziger, 1995), and (d) service needs of the adolescent father (Allen & Doherty, 1996;Resnick, Chambliss, & Blum, 1993).…”
Section: Adolescent Noncustodial Fathersmentioning
confidence: 99%